1999
DOI: 10.1068/p2845
|View full text |Cite
|
Sign up to set email alerts
|

Development of Illusory-Contour Perception in Infants

Abstract: We investigated whether infants from 8-22 weeks of age were sensitive to the illusory contour created by aligned line terminators. Previous reports of illusory-contour detection in infants under 4 months old could be due to infants' preference for the presence of terminators rather than their configuration. We generated preferential-looking stimuli containing sinusoidal lines whose oscillating, abutting terminators give a strong illusory contour in adult perception. Our experiments demonstrated a preference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…For infants, the likelihood of responding to subjective contours depends on the support ratio (Otsuka, Kanazawa, & Yamaguchi, 2004), overall size (Kavsek, 2002), and presence of motion cues (e.g., Curran, Braddick, Atkinson, Wattam-Bell, & Andrew, 1999). Young infants (3-and 4-month-olds) respond to subjective contours when the support ratio is high (66%) (Otsuka et al, 2004) or when motion is available (Curran et al, 1999;Johnson & Aslin, 1998). In addition, 4-month-olds respond to subjective contours in relatively small figures, whereas even 7-month-olds fail to do so in a large figure, suggesting a critical influence of the spatial separation between the inducers in infants' perception of subjective contours (Kavsek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For infants, the likelihood of responding to subjective contours depends on the support ratio (Otsuka, Kanazawa, & Yamaguchi, 2004), overall size (Kavsek, 2002), and presence of motion cues (e.g., Curran, Braddick, Atkinson, Wattam-Bell, & Andrew, 1999). Young infants (3-and 4-month-olds) respond to subjective contours when the support ratio is high (66%) (Otsuka et al, 2004) or when motion is available (Curran et al, 1999;Johnson & Aslin, 1998). In addition, 4-month-olds respond to subjective contours in relatively small figures, whereas even 7-month-olds fail to do so in a large figure, suggesting a critical influence of the spatial separation between the inducers in infants' perception of subjective contours (Kavsek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…because motion attracts the infants' attention, and apparently exerts a facilitating effect on the infants' performance in visual habituationdishabituation tasks (e.g. Curran et al, 1999).…”
Section: Stimulimentioning
confidence: 99%
“…We used illusory contours (Kanizsa, 1979) as visual targets because previous studies have consistently shown that infants prefer looking at stimulus arrays that induce illusory contours to looking at those that do not (Curran, Braddick, Atkinson, Wattam-Bell, & Andrew, 1999;Kavšek, 2002;Otsuka, Kanazawa, & Yamaguchi, 2004;Otsuka & Yamaguchi, 2003). In addition, Otsuka and colleagues reported that even 3-and 4-month-olds showed a preference for illusory contours when the support ratio was relatively high.…”
Section: Introductionmentioning
confidence: 98%